Childbirth care after the implementation of the Carioca Stork Program: the perspective of nursing - Ana Elisa Fernandes Lima; Leila Justino da Silva; Marianne de Lira Maia; Adriana Lenho de Figueiredo Pereira; Marcele Zveiter; Tânia Maria de Almeida Silva (Universidade Federal do Ceará, 2015)
Objective: to describe the actions recommended by the Carioca Stork Program for assistance to pregnant women and identifywhether the implementation of this program had repercussions on the assistance from the perspective of the nursingteam. Methods: descriptive study with a qualitative approach, conducted in a public maternity hospital. Semi-structuredinterviews were conducted with four obstetric nurses and seven nursing auxiliaries who work at the obstetric center of thismaternity hospital. We used the technique of thematic content analysis. Results: the study categories were: Qualification ofthe hospital obstetric care, care and professional repercussions from the Carioca Stork Program. Conclusion: the nursingstaff considered that the implementation of the program brought improvements in childbirth care, favored women's rightsand the performance of obstetric nursing in the municipal health network.